2007
DOI: 10.1108/03074350710753771
|View full text |Cite
|
Sign up to set email alerts
|

Empirical testing of the loss provisions of banks in the GCC region

Abstract: PurposeThe purpose of this study is to examine the factors which affect loss provision for loans and investment in Murabaha, Musharka, and Mudarabah for banks in the Gulf Cooperation Council (GCC) region. The effect of prior period earnings, legal and statutory reserves, size of the bank, level of debt, and loan and investment to deposit ratio on the loss provisions of banks are examined for the period 2000‐2003.Design/methodology/approachTo test the factors that explain the loan loss provision and to test the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
60
3
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 18 publications
(20 reference statements)
13
60
3
2
Order By: Relevance
“…On average, in Islamic banks, LLP and beginning non-performing loans represent, respectively, 1.38 and 4.3 percent of beginning loans. Our findings are consistent with those reported by Zoubi and Al-Khazali (2007), Taktak et al (2010b) and Quttainah (2011) who found that Islamic banks make a low estimation of loss provisions and non-performing loan. The mean ratio of change in total loan equals 60.81 percent, like Taktak et al (2010b) and Quttainah (2011), results in standard deviation indicating a large dispersion in the level of loans provided by Islamic banks.…”
Section: Descriptive Statisticssupporting
confidence: 96%
See 3 more Smart Citations
“…On average, in Islamic banks, LLP and beginning non-performing loans represent, respectively, 1.38 and 4.3 percent of beginning loans. Our findings are consistent with those reported by Zoubi and Al-Khazali (2007), Taktak et al (2010b) and Quttainah (2011) who found that Islamic banks make a low estimation of loss provisions and non-performing loan. The mean ratio of change in total loan equals 60.81 percent, like Taktak et al (2010b) and Quttainah (2011), results in standard deviation indicating a large dispersion in the level of loans provided by Islamic banks.…”
Section: Descriptive Statisticssupporting
confidence: 96%
“…There is no difference in the use of discretion by managers when reporting LLP between Islamic banks and their non-Islamic counterparts. This finding is in accordance with the one reported by Zoubi and Al-Khazali (2007), who found that Islamic and conventional banks follow the same way of provisioning.…”
Section: Islamic Banks Versus Conventional Banks (Panel B)supporting
confidence: 95%
See 2 more Smart Citations
“…The main objective of banks, whether Islamic banks or conventional banks, is to attract deposits and to reinvest those deposits to make profits (Zoubi and Al‐Khazali, ). Therefore, Hamdi and Zarai () find that Islamic banks also have incentives to manage earnings to achieve certain goals.…”
Section: Background and Hypotheses Developmentmentioning
confidence: 99%